Recommendations for high-risk clinical target volume definition with computed tomography for three-dimensional image-guided brachytherapy in cervical cancer patients. (10th November 2016) - Ohno, Tatsuya; Wakatsuki, Masaru; Toita, Takafumi; Kaneyasu, Yuko; Yoshida, Ken; Kato, Shingo; Ii, Noriko; Tokumaru, Sunao; Ikushima, Hitoshi; Uno, Takashi; Noda, Shin-ei; Kazumoto, Tomoko; et al.
Abstract: Our purpose was to develop recommendations for contouring the computed tomography (CT)-based high-risk clinical target volume (CTVHR ) for 3D image-guided brachytherapy (3D-IGBT) for cervical cancer. A 15-member Japanese Radiation Oncology Study Group (JROSG) committee with expertise in gynecological radiation oncology initiated guideline development for CT-based CTVHR (based on a comprehensive literature review as well as clinical experience) in July 2014. Extensive discussions occurred during four face-to-face meetings and frequent email communication until a consensus was reached. The CT-based CTVHR boundaries were defined by each anatomical plane (cranial–caudal, lateral, or anterior–posterior) with or without tumor progression beyond the uterine cervix at diagnosis. Since the availability of magnetic resonance imaging (MRI) with applicator insertion for 3D planning is currently limited, T2-weighted MRI obtained at diagnosis and just before brachytherapy without applicator insertion was used as a reference for accurately estimating the tumor size and topography. Furthermore, utilizing information from clinical examinations performed both at diagnosis and brachytherapy is strongly recommended. In conclusion, these recommendations will serve as a brachytherapy protocol to be used at institutions with limited availability of MRI for 3D treatment planning.